Inescapable tensions: performance and/or psychological well-being in Olympic and Paralympic athletes during sport disruption - Trainor, L. R.; Bennett, E. V.; Bundon, A. M.; Tremblay, M.; Mannella, S.; Crocker, P. R. E. (Qualitative Research in Sport, Exercise and Health, 2023)
Recently there has been a shift from exploring psychological distress to exploring psychological wellbeing (PWB) in the sport context (see Foskett & Longstaff, 2018; Gorczynski et al., 2017; McLoughlin et al. 2021; Moesch et al., 2018; Rice et al., 2016). Well-being in general refers to `optimal performance and functioning`(Deci and Ryan 2008, 1); however, well-being has two distinct perspectives that conceptualise well-being differently, the hedonic perspective (Tatarkiewicz 1976) and the eudaimonic perspective (Aristotle 1947). Hedonic well-being (synonymous with subjective well-being) is defined as experiencing a high level of positive affect, a low level of negative affect, and a high degree of life satisfaction (Deci and Ryan 2008; Diener 1984). In essence, this perspective focuses on maximising pleasure and minimising pain (Ryan and Deci 2001).